2014
DOI: 10.7448/ias.17.3.19151
|View full text |Cite
|
Sign up to set email alerts
|

Communicating about microbicides with women in mind: tailoring messages for specific audiences

Abstract: IntroductionCurrent HIV prevention options are unrealistic for most women; however, HIV prevention research has made important strides, including on-going development of antiretroviral-based vaginal microbicide gels. Nevertheless, social-behavioural research suggests that women's ability to access and use new HIV prevention technologies will be strongly influenced by a range of socio-cultural, gender and structural factors which should be addressed by communications and marketing strategies, so that these prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…HIV risk perceptions, sexual practices, condom use, and microbicide communication consideration were explored for each audience, including young women, female sex workers (FSWs), serodiscordant couples, and women in stable relationships. The results of the Kenya literature review, which have been published elsewhere (Sidibe et al, 2014), confirmed that young women, women in stable relationships (including HIV discordant couples), and FSWs all have difficulty using condoms all or some of the time. These findings underscore the need for a product like microbicides.…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…HIV risk perceptions, sexual practices, condom use, and microbicide communication consideration were explored for each audience, including young women, female sex workers (FSWs), serodiscordant couples, and women in stable relationships. The results of the Kenya literature review, which have been published elsewhere (Sidibe et al, 2014), confirmed that young women, women in stable relationships (including HIV discordant couples), and FSWs all have difficulty using condoms all or some of the time. These findings underscore the need for a product like microbicides.…”
Section: Methodssupporting
confidence: 69%
“…In Kenya, the highest proportion of new HIV infections occur within stable relationships (National AIDS Control Council [NACC], 2009), which is not surprising given that an estimated 11% of married or cohabitating men have multiple sex partners (Kenya National Bureau of Statistics [KNBS] and ICF Macro, 2010). Within such relationships, women find it difficult to request condom use, because it implies infidelity and may result in violence (Sidibe et al, 2014). Young women, including adolescents, are at especially high risk of HIV, due in part to their low HIV risk perception and challenges negotiating condom use with older male partners.…”
Section: Introductionmentioning
confidence: 99%
“…The need for more woman-centred HIV prevention technologies still remains a key priority, due to the existing hegemonic masculinities that still exist in South Africa (Jewkes and Morrell 2012). Despite common features/characteristics between oral and vaginal ARV-based HIV prevention products, their introduction strategies may require different approaches as messages must be tailored for different users with varying perceptions of risk, outcome expectations and barriers to action (Sidibe et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A second paper, by Sidibe et al . [ 21 ], describes potential barriers and facilitators of microbicide use by four end-user audiences in Kenya based on a literature review and an in-country policy consultation: female sex workers, women in stable and discordant relationships, and sexually active young women. These groups varied in the extent to which the salience of HIV prevention versus partner intimacy or sexual pleasure as a motivation for using a vaginal microbicidal gel might encourage or discourage their use of such a product.…”
Section: Understanding Needs Of Specific Groups Of End-usersmentioning
confidence: 99%